Effect of Cr Addition on Microstructure and Properties of AuGa Solder - Yu Tao; Songbai Xue; Han Liu; Weimin Long; Bo Wang (Metals, 2020)
In order to meet the service requirements of electronic devices working at 300 °C in the fields of energy resource prospecting and space exploration, Cr element was added to modify AuGa solder to improve its high-temperature performance. The results showed that the addition of 0.3 wt.% Cr element reduced the loss of Ga element in the smelting and casting process, and effectively improved the problem of the inhomogeneous microstructure of the solder matrix. On the basis of maintaining the good wettability of the solder, the addition of trace chromium effectively restrains the excessive flux of the solder, and the presence of chromium improves the oxidation resistance of the solder. Furthermore, Cr element optimized the interface morphology and improved the mechanical properties of the solder joint. The shear strength of the AuGa-0.3Cr/Ni joint was 87.2 MPa, which was 13.1% higher than that of the joint without Cr element. After 240 h of aging, the shear strength of the AuGa-0.3Cr joint was still the peak value at 84.1 MPa, which was 16.3% higher than that of the AuGa joint.